Employing Blended Literature Circles to Foster Activating Academic Emotions of Struggling Readers - David Imamyartha; Eka Wahjuningsih; Areta Puspa; Mitasari Mitasari; Siti Masrifatul Fitriyah; Rizki Febri Andika Hudori; Rika Andayani; Zakiyah Tasnim; Aan Erlyana Fardhani; Siti Sundari; Bambang Arya Wijaputra (Indonesian Research Journal in Education |IRJE|, 2021)
Grounded within academic emotion and transactional reading theory, the present study investigates the understudied struggling readers’ academic emotions after taking part in three blended literature circles in an English class at tertiary education. Thirteen Physics Education students partook in the research. Data were garnered by open-ended questionnaires and semi-structured interviews, the results of which were analyzed by directed content analysis bound to Academic emotion theory. The research findings explicate that blended literature circles pave the path to propelling reading-to-learn endeavors. Despite sub-optimal reading proficiency, the students’ academic emotions depict the efforts towards achievement goals, primarily laden with a mastery approach, and social goals through dialogic reading in blended literature circles.